2000
DOI: 10.1021/bi002472w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Rescue of Phosphoryl Transfer in a Cavity Mutant:  A Cautionary Tale for Site-Directed Mutagenesis,

Abstract: We have explored the ability of a nucleoside diphosphate kinase (NDPK) mutant in which the nucleophilic histidine has been replaced by glycine (H122G) to transfer phosphate from ATP to alcohols of varying pK a , size, shape, and polarity. This cavity mutant does indeed act as a primitive alcohol kinase. The rate of its phosphoryl transfer to alcohols varies considerably, with values spanning a ∆∆G ‡ range of 4 kcal/mol, whereas the alcohols have very similar intrinsic reactivities. Analysis of these results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The comparatively better rescue of Gly substitutions than Ala for the critical His in both SCMV and HCMV assemblin is attributed to the smaller size and greater structural flexibility of Gly, allowing imidazole a better functional fit at the mutant His position (37). This interpretation is consistent with (i) the inability of imidazole to enhance activity of a mutant containing the larger Gln substitution (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The comparatively better rescue of Gly substitutions than Ala for the critical His in both SCMV and HCMV assemblin is attributed to the smaller size and greater structural flexibility of Gly, allowing imidazole a better functional fit at the mutant His position (37). This interpretation is consistent with (i) the inability of imidazole to enhance activity of a mutant containing the larger Gln substitution (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…NAD(P)H, in contrast, is anchored mostly via the pyrophosphate moiety, allowing the nicotinamide ring to adopt different conformations. However, given the inherent context dependence of any energetic effect caused by site-directed mutagenesis, 18,19 we admit that more detailed studies are necessary to gain insight into the role(s) of Trp358 in the reductive half-reaction.…”
Section: Trp358-decreasing the Activation Energy In The Reductive Halmentioning
confidence: 99%
“…Previous studies have demonstrated that the hydrogen bond acceptor ability of C]S versus C]O is significantly reduced. [36][37][38][39][40] The P(K1) location was chosen because the bH81N mutation produces a particularly large effect on dissociation rates. It was also chosen because the bHis81 sidechain is a surface residue that can easily rotate the w58 about C a -C b dihedral to accommodate the slightly longer C]S hydrogen bond, which has been measured to be about 0.9 Å longer than C]O hydrogen bonds in a-helices and b-sheets.…”
Section: Dissociation Kinetics Of Hydrogen Bond Mutantsmentioning
confidence: 99%